'Good Women do not Inherit Land' : Politics of Land and Gender in India - Rao, Nitya (Abingdon, Oxon ; New York : Routledge, 2018)
"Land for the adivasi Santal women in Dumka, Jharkhand stands for security, social position and identity, and in this men have a distinct advantage. The time period covered is from historic times to the present. The role of government administrative bodies, NGOs and political leaders is also emphasized.Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka"--Provided by publisher.
chapter 1 Introduction -- chapter 2 A Personal Journey -- chapter 3 Faces of Poverty: The Villages Profiled -- chapter 4 Reinventing Tradition: Agrarian Movements in History -- chapter 5 Land as a Productive Resource -- chapter 6 Locating Identities -- chapter 7 Women$1 (Bs Claims to Land -- chapter 8 Custom and the Courts: Bargaining with Modernity -- chapter 9 Development Interventions: Does One Size Fit All? -- chapter 10 Reframing the Debate: Challenges and Dilemmas.s
Includes bibliographical references.
Keywords: Women's rights -- India; Landowners -- India